Exploring Local Wisdom for Holistic Wellness Tourism in an Island Destination: Evidence from Bintan Regency, Indonesia - Putri Fistyaning Army; Indah Andesta; Mashudi Mashudi; Andiko Firlansyah; Hilda Yunita (LPPM STIE KRAKATAU, 2026)
Wellness tourism is increasingly shifting toward authentic experiences rooted in local culture and natural environments. This study explored how local wisdom can serve as the foundation for holistic wellness tourism development in Bintan Regency, Indonesia. This study employed an exploratory qualitative design using the holistic wellness framework of body, mind, spirit, and environment. Data were collected through participant observation, semi-structured interviews, and document analysis involving seven purposively selected tourism stakeholders and community representatives. The data were analyzed using reflexive thematic analysis. The findings reveal that the body dimension is reflected through coastal physical activities, traditional cuisine, herbal beverages, and indigenous body treatments. The mind dimension emerges from environmental education and mindfulness experiences, while the spirit dimension is expressed through cultural participation and contemplative activities. The environment dimension is supported by conservation practices, visitor-capacity management, ecological interpretation, and responsible destination management. Local wisdom provides a culturally grounded and sustainable foundation for integrating the physical, psychological, spiritual, and environmental dimensions of holistic wellness tourism. This study is limited to a qualitative exploration in Bintan Regency involving a small number of stakeholders, which may restrict the generalizability of the findings to other tourism destinations. This study contributes a context-sensitive framework for community-based wellness tourism development that strengthens local identity, community participation, and environmental sustainability while providing practical guidance for destination management organizations.